From Planning Commission to NITI Aayog -India’s Transition to Cooperative Federalism. - Latief Ahmad Lone; Reyaz Ahmad Mir (RADJA PUBLIKA, 2025)
The Planning Commission an erstwhile extra constitutional body was set up in March 1950, constituted a “one Size fits all approach “as acclaimed by the Union Government. The Modi government abolished the planning Commission on 13th August 2014 and on that place the NITI Aayog was installed to actualise the important goal of cooperative federalism and to enable good governance in India. On the promise that strong states make a strong nation, NITI Aayog acts as the quintessential platform for the government of India by bringing states together as ‘Team India’ to work towards the national development agenda.